An autobiography or the story of my experiments with truth a critical edition - Gandhi, M K. (New Haven Yale University Press, 2018)
Gandhi's non-violent struggles against racism, violence, and colonialism in South Africa and India had brought him to such a level of notoriety, adulation that when asked to write an autobiography midway through his career, he took it as an opportunity to explain himself. He feared the enthusiasm for his ideas tended to exceed a deeper understanding of his quest for truth rooted in devotion to God. His attempts to get closer to this divine power led him to seek purity through simple living, dietary practices, celibacy, and a life without violence. This is not a straightforward narrative biography, in The Story of My Experiments with Truth, Gandhi offers his life story as a reference for those who would follow in his footsteps.